ROLE OF MULTILATEATION IN AIR TRAFFIC SAFETY ENHANCEMENT (Perner's Contacts, 2011)
This article describes multilateration surveillance systems and their impact on increase in capacity and safety of air traffic. The work includes a description of multilateration systems and used methods of signal processing – central and distributed time architecture. Conclusion of this work deals with multilateration systems in various flight phases and their benefits for flight.
Keywords: Multilateration; Central Time; Distributed Time; Surface Multilateration; Wide Area Multilateration